2018
DOI: 10.15252/embj.201797822
|View full text |Cite
|
Sign up to set email alerts
|

Prion‐like protein aggregates exploit the RHO GTPase to cofilin‐1 signaling pathway to enter cells

Abstract: Protein aggregation is a hallmark of diverse neurodegenerative diseases. Multiple lines of evidence have revealed that protein aggregates can penetrate inside cells and spread like prions. How such aggregates enter cells remains elusive. Through a focused siRNA screen targeting genes involved in membrane trafficking, we discovered that mutant SOD1 aggregates, like viruses, exploit cofilin-1 to remodel cortical actin and enter cells. Upstream of cofilin-1, signalling from the RHO GTPase and the ROCK1 and LIMK1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
1
18
2
Order By: Relevance
“…For example, Fascin is a critical component downstream of Rac1 that is needed for actin cytoskeletal organization and cell motility . RhoA regulates phosphorylation of cofilin‐1 and activity of annexin A2, thereby regulating cytoskeletal organization and cell adhesion .Therefore, we wondered if RhoA and Rac1 were added to the network analysis. Interestingly, these proteins were linked together and an integrated network was shown when RhoA and Rac1 were added to the analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Fascin is a critical component downstream of Rac1 that is needed for actin cytoskeletal organization and cell motility . RhoA regulates phosphorylation of cofilin‐1 and activity of annexin A2, thereby regulating cytoskeletal organization and cell adhesion .Therefore, we wondered if RhoA and Rac1 were added to the network analysis. Interestingly, these proteins were linked together and an integrated network was shown when RhoA and Rac1 were added to the analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study by our group demonstrated that silencing of cofilin inhibits PMA- and growth factor-induced membrane ruffling and macropinocytosis in macrophages (10). Recently, Zhong et al, using pharmacological and genetic approaches have shown an important role for cofilin and actin polymerization in macropinocytic entry of prion-like protein aggregates in neuroblasts (63). The results of the present study demonstrated that PMA and HGF treatments dephosphorylate cofilin at Ser-3 in wild-type macrophages and activation of cofilin is significantly attenuated in PKCδ knockout macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently unclear what the major mechanism of synaptic tau secretion is, but the evidence so far suggests: (1) release from synaptic vesicles [242] (2) secretion in extracellular vesicles such as exosomes [241, 256, 313] and ectosomes [80], (3) direct translocation across the membrane [157, 208] or (4) tunneling nanotubes [1, 295]. Similarly, several tau uptake mechanisms have been identified which are not mutually exclusive: (1) bulk endocytosis [98, 121, 259, 317] macropinocytosis by heparin sulfate proteoglycans [84, 132, 162, 248, 288, 328] or (3) clathrin-mediated endocytosis [49, 82]. After tau seeds enter the neuron they can seed physiological monomers, thereby propagating the disease process [85].…”
Section: Introductionmentioning
confidence: 99%